Economic Analysis of Seed Inoculation and Phosphorus Doses Application in Cowpea (Vigna unguiculata L.) - Ankita Poudel (Turkish Journal of Agriculture: Food Science and Technology)
The study about the economic returns of cowpea (Vigna unguiculata) by the use of rhizobium seed inoculation and different phosphorus doses was conducted at Bharatpur, Chitwan, from February to May 2022. The experiment was conducted in a two-factor randomized complete block design (RCBD) with three replications and eight treatments. Treatments were set as factor A: seed inoculation i.e., un-inoculated and inoculated; and factor B: four different phosphorus doses (20, 40, 60, 80 kg ha-1). The cowpea variety ‘Prakash’ was used. Results revealed that the application of seed inoculation provides the highest returns compared to an un-inoculated one; similarly, in case of phosphorus dose of 40 kg P2O5 ha-1 gives the maximum economic returns compared to other phosphorus doses. Furthermore, the interaction of rhizobium inoculation with 40 kg ha-1 gives the highest gross income (NRs. 216005), net return (NRs. 110829.39) and B: C (2.05) compared to all other single inoculation or phosphorus or interaction treatments ( 1 $ = NRs. 132.53) . From the result, it is concluded that the use of rhizobium inoculation along with 40 kg P2O5 ha-1 would be economically profitable for the farmers under the Terai conditions of Nepal.